Translation North and South: Composing the Translator’s Archive - Guzmán, María (TTR, 2013)
One of Daniel Simeoni’s major contributions to translation thinking is his investigation of the translator as an agent of cultural production. This approach to the translator, in Simeoni’s view, originates in a strong sense of social and geopolitical situatedness. Based on this perspective and drawing on Simeoni’s arguments and in particular on his call to develop translators’ “sociographies,” in this paper I posit the notion of the “translator’s archive” as an epistemological and methodological possibility to study the translator and for a geneology of translation praxis. I investigate the significance of the “translator’s archive” in particular to understand the place of literary translators and their social situatedness and agency in the context of the Americas.